Deprivation as a Causal Factor for Child Labour:A Case Study from Sikkim - Bansal, Anamika (Arthshastra Indian Journal of Economics & Research, 2016)
Poverty is well recognized as an important supply side factor on the child labour issue. The paper explored this relationship in a situation where a household is compelled to send their children to work because of the concern of the parents for household survival. Instead of measuring poverty in a traditional way, which is exclusively interpreted in monetary terms, this study explained the link between child labour and poverty in a more expanded and meaningful way in the form of deprivation. With a particular empirical focus on Sikkim, which is one of the most neglected and untouched areas with regard to child labour research in spite of being ranked first in terms of work participation rate of children in 2001 Census, the paper tried to answer the question of whether the attainment of basic capabilities reduces child labour. With this purpose in mind, poverty was measured in a multi-dimensional approach, where a human deprivation index was constructed on the basis of the lack of basic infrastructural facilities in three respects, that is, education, health, and standard of living. In the latter part of the paper, the Pearson correlation coefficient was used as a measure of the degree of association between deprivation and child labour hours. As expected, child labour is treated as an increasing function of human deprivation. The study also showed the intensity of child labourers across different income classes in Sikkim by using the goodness of fit test. In case of the low income classes, the number of children in the labour force is likely to be higher up.